Cell death in acute lung injury: caspase-regulated apoptosis, pyroptosis, necroptosis, and PANoptosis - Xiao, Jun; Wang, Lichuan; Zhang, Bohan; Hou, Ana (Frontiers in Pharmacology, 2025)
There has been abundant research on the variety of programmed cell death pathways. Apoptosis, pyroptosis, and necroptosis under the action of the caspase family are essential for the innate immune response. Caspases are classified into inflammatory caspase-1/4/5/11, apoptotic caspase-3/6/7, and caspase-2/8/9/10. Although necroptosis is not caspase-dependent to transmit cell death signals, it can cross-link with pyroptosis and apoptosis signals under the regulation of caspase-8. An increasing number of studies have reiterated the involvement of the caspase family in acute lung injuries caused by bacterial and viral infections, blood transfusion, and ventilation, which is influenced by noxious stimuli that activate or inhibit caspase engagement pathways, leading to subsequent lung injury. This article reviews the role of caspases implicated in diverse programmed cell death mechanisms in acute lung injury and the status of research on relevant inhibitors against essential target proteins of the described cell death mechanisms. The findings of this review may help in delineating novel therapeutic targets for acute lung injury.